Gene Editing Frontiers: CRISPR-Cas9 as a Novel Therapeutic Approach for Autism Spectrum Disorder - Deshmukh, Arya; Sheikh, Mujibullah; Dange, Akanksha (International Journal of Pharmaceutical Investigation, 2026)
Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by deficits in social interaction and communication alongside repetitive behaviors and restricted interests. Despite substantial progress in identifying genetic and molecular contributors, effective disease-modifying therapies remain limited. The CRISPR-Cas9 gene-editing system has emerged as a powerful tool for unraveling the complex genetic architecture of ASD and developing targeted therapeutic strategies. This review explores the mechanistic principles of CRISPR-Cas9, including its molecular components, DNA repair pathways, and innovations in delivery systems for central nervous system targeting. We examine the CRISPR-mediated development of in vitro and in vivo ASD models spanning from iPSC-derived neurons to nonhuman primates and evaluate their translational relevance. Additionally, this review highlights the therapeutic applications of CRISPR in correcting pathogenic mutations, modifying epigenetic states, and modulating gene expression in both syndromic and nonsyndromic ASD. Critical challenges such as immune responses, mosaicism, and off-target effects are discussed, alongside emerging solutions, including anti-CRISPR proteins, base editing, and tissue-specific delivery systems. Finally, we assess the future prospects of integrating CRISPR technology with personalized medicine to advance ASD diagnosis, prevention, and treatment.
Keywords: Autism Spectrum Disorder (ASD); CRISPR-Cas9; Gene Editing; Therapeutic Strategies; Cellular Models